Uniaxial performance of circular hybrid fibre-reinforced lightweight aggregate concrete columns. (1st July 2021) - Wu, Tao; Sun, Lixin; Wei, Hui; Liu, Xi
Highlights: Compressive performance of spirally confined fibre-reinforced LWAC was investigated. Crack propagation, peak stress, peak strain, and ductility of the column were discussed. Carbon fibres enhanced the ductility of LWAC to a greater extent than polypropylene fibres. Identical volumetric fraction of the two fibres were optimum to improve the ductility of confined LWAC. A confinement model applicable to hybrid fibre-reinforced LWAC columns was proposed. Abstract: To investigate the compressive performance of fibre-reinforced concrete columns, 20 circular columns with a consistent size of Φ 250 × 750 mm were tested, considering different concrete types, steel spiral spacing, fibre types, and volumetric fibre fractions. Polypropylene fibres prevented the initial cracking and premature spalling of the cover more obviously than carbon fibres. The compressive strength of spirally confined lightweight aggregate concrete (LWAC) was improved to 1.45 times the unconfined strength, and the fibre-reinforced LWAC exhibited a greater enhancement in the compressive strength provided by the confining pressure than the plain LWAC. The incorporation of both single carbon fibres and hybrid carbon–polypropylene fibres enhanced the ductility of LWAC columns, while the polypropylene fibres exhibited an insignificant influence on the compressive properties of LWAC. Identical volumetric fractions of the two fibres contributed more significantly to the ductility of LWAC. Concerning the improved peak strain and residual strength, a confinement model of fibre-reinforced LWAC that accounted for the superposition of individual confinement effects, including lateral reinforcement and fibres, was proposed and compared with the experimental results. The predictions exhibited better agreement with the experimental curves than the existing typical models.